1977
DOI: 10.2134/jeq1977.00472425000600040014x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Cycling of Major and Trace Elements in Two Central European Forest Ecosystems

Abstract: Concentrations and annual fluxes of K, Na, Ca, Mg, Al, Fe, Mn, Zn, N, S, P, Cr, Cu, Ni, Pb, Sb, Bi, Cd, Hg, and Tl were measured in the precipitation input to the forest canopy, in precipitation beneath canopy, and in the seepage water below the humus layer and below the tree root zone (output) both in a Central European beech (Fagus silvatica) and in a spruce (Picea abies) forest. Concentrations were determined in an acid loess loam soil from the beech site and in a calcareous little‐weathered loess C‐horizon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
4
4

Year Published

1978
1978
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 159 publications
(47 citation statements)
references
References 0 publications
1
38
4
4
Order By: Relevance
“…2 (Foster et al 1985 tation range from about 3 kg N ha-t yr-t (Carlisle etal. 1966:' Nihlgard 1970Mahendreppa and Ogden 1973;McColl et al 1982) in relatively unpolluted areas to 20 kg N ha-I yr-I in polluted areas (Heinricks and Mayer 1977;Likens et al 1977 (Miller 1968 (Melillo and Gosz 1983 Mahendrappa and Kingston (1980) (Berg and Staaf 1980;Melillo et al 1982) and in some coniferous forest organic horizons the availability of C can limit microbial activity (Salonius 1978;Foster et al 1980). The results from a model developed by Bosatta and Staaf (1982) For personal use only.…”
Section: Nutrient Accumulation In the Forestmentioning
confidence: 99%
“…2 (Foster et al 1985 tation range from about 3 kg N ha-t yr-t (Carlisle etal. 1966:' Nihlgard 1970Mahendreppa and Ogden 1973;McColl et al 1982) in relatively unpolluted areas to 20 kg N ha-I yr-I in polluted areas (Heinricks and Mayer 1977;Likens et al 1977 (Miller 1968 (Melillo and Gosz 1983 Mahendrappa and Kingston (1980) (Berg and Staaf 1980;Melillo et al 1982) and in some coniferous forest organic horizons the availability of C can limit microbial activity (Salonius 1978;Foster et al 1980). The results from a model developed by Bosatta and Staaf (1982) For personal use only.…”
Section: Nutrient Accumulation In the Forestmentioning
confidence: 99%
“…Swanson and Johnson (1980) found that bulk precipitation input of Fe far exceeded output (deep seepage + streamflow) in a forested watershed in the New Jersey Pine Barrens. Heinrichs and Mayer (1977) reported Fe budgets for a 125-year-old beech forest and an 85-year-old spruce forest in central Germany's Solling hill region. At both sites, bulk precipitation inputs of Fe exceeded deep seepage, indicating net retention of Fe.…”
Section: Introductionmentioning
confidence: 99%
“…Nihlgard 1970;Mayer 1974;Abrahamsen et a/. 1977;Heinrichs & Mayer 1977;Mayer & Ulrich 1978). The dry deposition of sulfur species increases in the order bare soil, deciduous forest, coniferous forest.…”
Section: Sulfur Metabolismmentioning
confidence: 99%